Twitter Social Network Interaction As Customer Engagement In Competition For E-Commerce E-Health Performance In Indonesia - Annisa Nur Navisha; Rita Ambarwati; Misti Hariasih (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2023)
Background – The presence of e-commerce e-health is a societal solution to health needs in the era pandemic. Social distancing rules cause considerable restrictions on community socialization, so they use social media alternatives to share experiences. That matter causes customers to talk about the performance of digital e-health services and create consumer engagement. Public opinion and ratings on social media become data information analyzed to improve service quality. Aim – This study aims to identify customer conversations on Twitter about e-commerce e-health to see its performance and compare e-health results networks in Indonesia. Design / methodology / approach – The research method in this study is the Social Network Analysis (SNA) approach and descriptive meaning to get the results of the formulated goals. Findings – The results of this study showed that pre-pandemic e-health users in Indonesia were more dominant in utilizing psychologist and psychiatric consultations and buying easy and practical medicines. During the pandemic, customers more often used doctor consultations related to symptoms and treatment of Covid-19, drugs and vitamins for self-isolation, supported by online payments. Research implication – This research contributes to e-health companies in Indonesia regarding suggestions for utilizing SNA through customer interaction on social media to improve the performance and competition of e-health services and determine superior strategies. Limitations – This research explores data only from social media Twitter, based on the material for data visualization is only in text. The scope of the study is only in the health business, so it can further develop in other sectors.